THE HIDDEN COGNITIVE BURDEN OF CHILDHOOD IRON DEFICIENCY ANEMIA: EVIDENCE FROM GLOBAL STUDIES - Endang Mariani; Nova Lidia Sitorus; Rachel Amanda; Saskia Piscesa (PT. Varians Statistik Kesehatan, 2026)
Introduction: Iron Deficiency Anemia (IDA) remains one of the most significant public health problems worldwide. Prior studies have shown associations between low iron status/iron deficiency anemia and poor child development outcomes. Studies suggested IDA among younger children may cause permanent cognitive and/or developmental disabilities. Methods:Literature search was conducted across PubMed, Scopus, and Google Scholar for studies published between2006 and 2025. Search terms included “anemia,” “children,” “pediatric,” “iron deficiency,” “cognitive,” “child development,” and “child nutrition.”Inclusion criteria of this review: pediatric populations (0–18 years), anemia-supplementation interventions, and outcomes related to nutrition, biochemical markers, or nutritional status. Fifteen core studies (RCTs, systematic reviews, meta-analyses, and narrative reviews) met all inclusion criteria. Results:The reviewed studies demonstrate that anemiain children, primarily due to iron deficiency, is associated with impaired cognitive and developmental outcomes. Iron deficiency affects brain development by disrupting oxygen delivery, myelination, and neurotransmitter function, particularly during early growthperiod in which it is critical. The biological effectis linked to deficits in attention, memory, learning performance, and school readiness. Based on the evidence,further suggests that these early impairments may persist into later educational and economic disadvantages, contributing to a profound long-term loss of human capital. Conclusion:Childhood anemia, especially IDA, is evidently associated with impaired cognitive and developmental outcomes. Early prevention, screening, and appropriate iron interventions are essential to protect neurodevelopment and support long-term human capital formation.